The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ejlt.202100063
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Oil–Beeswax Oleogels Are Promising Frying Medium for Potato Strips

Abstract: Sunflower oil-beeswax oleogels at 3% (BWO-3) and 8% (BWO-8) organogelator concentration are prepared to evaluate oleogels as frying medium for potato strip frying against commercial sunflower oil (SO). Rheological and thermal analyses of oleogels prove that the samples are fully solid (20±3°C) and totally liquid (180°C), and thermoreversible. Fresh and used (after frying) fat analyses show that free fatty acidity (FFA), peroxide value (PV) and total polar materials (TPM) are enhanced in all samples at the 7th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
(70 reference statements)
3
19
1
Order By: Relevance
“…The color characteristics of SDEW instant noodles that are fried in different oleogel frying mediums are shown in Figure 1 A–D. Generally, in fried food products, the color characteristics play an important sensory role in the overall acceptability [ 9 ]. In general, the OGU-fried samples had the highest L*, b*, and lowest a* values, whereas the PO-fried samples showed the lowest L*, b*, and highest a* values ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The color characteristics of SDEW instant noodles that are fried in different oleogel frying mediums are shown in Figure 1 A–D. Generally, in fried food products, the color characteristics play an important sensory role in the overall acceptability [ 9 ]. In general, the OGU-fried samples had the highest L*, b*, and lowest a* values, whereas the PO-fried samples showed the lowest L*, b*, and highest a* values ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a rough noodle surface ( Figure 4 ) leads to increased oil absorption of the product [ 34 ], which can be seen in that the PO-fried noodles had a greater oil uptake and lowered the cooking yield as compared with the OG- and OGU-fried noodles (see Figure 2 A,B). The gelling effect of oleogel could also be attributed to the uniform and smooth surface of the instant noodles, as they can rapidly solidify at ambient temperature as compared to PO, which is liquid and free flowable [ 9 ]. Xiao et al [ 35 ] reported that, normally, plant lipids are flowable and easily exudate from the surface of the food products, causing an unfavorable morphological appearance on the food, whereas the oleogel has strong crystallization, which leads to minimal structural changes in the food products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations